A randomised, double-blind trial comparing raloxifene HCl and continuous combined hormone replacement therapy in postmenopausal women: Effects on compliance and quality of life - (:unkn) unknown (My University, 2002)
Objective: To compare continuous combined hormone replacement therapy (ccHRT) and raloxifene with respect to compliance and quality of life, which were predefined secondary endpoints of a large, prospective study designed to investigate the uterine effects of both treatments. Design: Double-blind, randomised controlled trial of six-month duration. Setting: One hundred and twenty-nine gynaecology hospital departments, clinics or practices specialised in women's healthcare, located in Europe, South Africa and Israel. Population: Healthy postmenopausal women (n = 1008). Main outcome measures: Changes in quality of life using the Women's Health Questionnaire (WHQ) and compliance using a compliance questionnaire and pill count. Adverse event and early discontinuation rates and satisfaction with treatment using a visual analogue scale (VAS). Results: Women taking raloxifene reported greater satisfaction with their treatment as assessed on the VAS (P = 0.004),and a lower proportion, as compared with ccHRT, reported being worried by the treatment (9.6% vs 20.2%, P < 0.01). Women taking ccHRT reported greater deterioration in scores from the WHQ for depressed mood and menstrual symptoms than those taking raloxifene (P < 0.01). For memory, vasomotor symptoms and sexual behaviour, the ccHRT group reported significantly greater mean improvements (P < 0.05). Over half (58.8%) of those taking raloxifene noticed no effect, 37.7% felt better and 3. 4% felt worse as measured using the compliance questionnaire. Fifty percent of the women taking ccHRT felt better, 37.8% noticed no effect but over 10% felt worse. More women on raloxifene (94.6%) than on ccHRT (85.9%) reported that they were taking their double-blinded medication regularly (P < 0.01). Conclusions: A lower rate of adverse event-related discontinuations, the lack of negative effects on quality of life and a smaller proportion of women being worried by the drug treatment were associated with higher treatment satisfaction and better compliance in postmenopausal women taking ccHRT or raloxifene.